Baring Our Soles - Yellow Light Breen (Journal of Research in Rural Education, 1996)
As I packed up to come to Harvard College 7 years ago, I received an earnest letter from my roommate-to-be, Randy Bruce. Randy, a high-school football star from the small farm town of Princeton in western Kentucky, was anxious to assure me that despite rumors to the contrary, folks in his part of Kentucky really do wear shoes! I came to know Randy to be a remarkable person, someone who had traversed a rough road to arrive at Harvard. He was raised by a tough single mom, literally on the wrong side of the tracks, and spoke the language of populists and intellectuals alike. On such a road, it was vital to be well shod.